URGENSI KAIDAH ‘ĀMM DALAM MEMAHAMI AYAT PERANG - Lufaefi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
The knowledge of the Qur'an is important to guide in interpreting the verses of the Qur'an, including the verses of jihād and qitāl. It is the rule of 'amm which is one of the basic principles in the science of the Qur'an, it is important in understanding and interpreting the verses of warfare so as not to misunderstand jihad with the intent of terrorism. Jihād / qitāl verses such as some of them QS. Al-Baqarah verse 191 and QS. At-Taubah verse 36. The two verses in the viewpoint of the rule of 'amm do not mean a war commandment in general with no justified background. With the takhsis al-'amm al-'aqli and sighah conditions, the two verses above command war only if the enemies of Islam fight or expel the believers first